Type of paternal sperm exposure before pregnancy and the risk of preeclampsia: A systematic review. (August 2020) - Di Mascio, Daniele; Saccone, Gabriele; Bellussi, Federica; Vitagliano, Amerigo; Berghella, Vincenzo
Highlights: Paternal sperm exposure in nulliparous women and sexual cohabitation > 12 months before pregnancy are associated with a decreased risk of preeclampsia. Abstract: Objective: The aim of this systematic review was to evaluate the role of paternal sperm exposure before pregnancy on the risk of preeclampsia. Study design: The search was conducted using electronic databases from inception of each database through October 2019. Review of articles also included the abstracts of all references retrieved from the search. Only studies evaluating exposure to paternal sperm before pregnancy on the risk of preeclampsia in the subsequent pregnancy were included. Exposure group was defined as significant exposure to paternal sperm, either measured by sexual cohabitation, oral sex habit, or by absence of barrier methods. Control groups was defined as minimal exposure to paternal sperm, either measured by lack of sexual cohabitation or oral sex habit, or by use of barrier methods. Sperm exposure identifiable before pregnancy that may be suspected to modify the risk of preeclampsia was examined. The primary outcome was the incidence of preeclampsia. Subgroup analyses by parity and type of sperm exposure were planned. All analyses were carried out using the random effects model. The pooled results were reported as the OR with 95 % confidence interval (CI). Heterogeneity was measured using I-squared (Higgins I 2 ). Results: Seven studies including 7125 pregnant women were included in this systematic review. Overall, the incidence of preeclampsia was similar in women with a higher overall sperm exposure compared to controls, 774/5512 (14 %) vs 220/1619 (13.6 %); OR 1.04, 95 % CI 0.88–1.22, respectively. The incidence of preeclampsia was significantly reduced in women with a higher overall sperm exposure when including only nulliparous women, 643/3946 (16.1 %) vs 170/725 (23.4 %); OR 0.63, 95 % CI 0.52 to 0.76. Significant lower rate of preeclampsia was also found for ≥12-month sexual cohabitation, 494/3627 (13.6 %) vs 123/691 (17.8 %); OR 0.73, 95 % CI 0.59−0.90. Significantly higher rate of preeclampsia was reported in women not using barrier methods, 315/1904 (16.5 %) vs 103/962 (10.7 %); OR 1.65, 95 % CI 1.30–2.10. Conclusions: Paternal sperm exposure in nulliparous women and sexual cohabitation > 12 months before pregnancy are associated with a decreased risk of preeclampsia.